2023
DOI: 10.3390/rs15061581
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Optical Properties and Types over Southern Africa and Reunion Island Determined from Ground-Based and Satellite Observations over a 13-Year Period (2008–2021)

Abstract: Fires occur seasonally in Southern Africa, from June to November, increasing tropospheric aerosol loading and triggering harmful consequences for the environment and human health. This study aims to examine 13 years of aerosol optical characteristics and types over Southern Africa and Reunion Island. Using AERONET sun photometers and MODIS observations, we found that a high aerosol optical depth and Angström exponent are associated with two predominant types of aerosols (biomass burning/urban industrial and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 76 publications
7
9
0
Order By: Relevance
“…Furthermore, a comparison of the seasonal AAOD showed that the least value is almost half of the highest value. It should be recalled that the peak of AAOD corresponds with the biomass-burning period (SON) in South Africa (see Kumar et al 2014;Ranaivombola et al 2023). This implies that more than 50% of the absorbing aerosols may be attributed to biomass-burning related.…”
Section: Omi Absorbing Aerosol Optical Depthmentioning
confidence: 99%
“…Furthermore, a comparison of the seasonal AAOD showed that the least value is almost half of the highest value. It should be recalled that the peak of AAOD corresponds with the biomass-burning period (SON) in South Africa (see Kumar et al 2014;Ranaivombola et al 2023). This implies that more than 50% of the absorbing aerosols may be attributed to biomass-burning related.…”
Section: Omi Absorbing Aerosol Optical Depthmentioning
confidence: 99%
“…CC BY 4.0 License. et al, 2017;Ranaivombola et al, 2023), India (Kaskaoutis et al, 2009;Patel et al, 2017), Buenos Aires (Cúneo et al, 2022) and Australia (Yang et al, 2021). In this study, we classified aerosols by using the following parameters: AOD, AE, EAE, SSA, and FMF, and a variety of threshold values (Figure 2) and all-point data to have the largest amount of data.…”
Section: Introductionmentioning
confidence: 99%
“…This method was already used in several works over South Africa (Kumar et al, 2017(Kumar et al, , 2020Ranaivombola et al, 2023). The BB/UR aerosol types can be distinguished using SSA, in combination with the EAE size indicator.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations